Are soils forming on buildings indicators of pollution in the city? A case study from Lublin (Eastern Poland) - Szafran, Tomasz; Plak, Andrzej; Chodorowski, Jacek; Telecka, Małgorzata (Quaestiones Geographicae, 2025)
The aim of the study was to determine the suitability of building-forming soils (edifisols) for assessing the pollution of urban areas, using a medium-sized city in Poland E as an example. The research hypothesis was that these soils, due to their specificity and occurrence, could be indicators of environmental degradation, with a particular focus on elevated trace element contents resulting from intensive anthropopression in urbanised areas. Eight soil profiles were selected, of which 14 soil samples were taken. The samples were taken from buildings of different ages and uses. Selected soil properties were then determined: particle size distribution, pH, organic carbon (OC), CaCO3, hydrolytic acidity (HA) and base exchange capacity (BEC) values, the effective cation exchange capacity (ECEC) and base saturation (BS). Metals present in high concentrations included Cd, Ni, Cu, Cr and Zn. Based on calculation of selected geochemical indices such as enrichment factor (EF), geoaccumulation index (Igeo), pollutant load index (PLI) and ecological risk index (RI), it was found that the investigated soils, characterised by elevated content of heavy metals of anthropogenic origin, can be considered as indicators of environmental pollution. The geochemical indices used in this study allowed us to demonstrate that the investigated soils are characterised by an elevated content of heavy metals of anthropogenic origin, and that soils formed on buildings can be indicators of the environment. The use of edifisols as indicators of pollution could make a significant contribution for a better assessment of the city’s ecosystem in the future.